Linking of taxpayer awareness to taxpayer compliance: The moderating role of account representative employee’s performance - Gunawan, Gunawan; Ridjal, Syamsul; Jamali, Hisnol (Archives of Business Research, 2018)
The purpose of this paper is to suggest and empirically test a model that explains the linking of taxpayer awareness on taxpayer compliance. In this model, account representative employee’s performance as a moderator variable. A valid research instrument was utilized to conduct a survey of 100 individual taxpayers registered in Tax Offices (KPP) Pratama North Makassar (Indonesia). The model was tested by using the partial least squares (PLS) structural equation modeling technique on the software WarpPLS, version 5.0. A thorough analysis of the role of moderator was carried out. Findings provide support for the proposed model and show that taxpayer compliance depend on taxpayer awareness as well as account representative employee’s performance level. These relationships are moderated by account representative employee’s performance. The model exhibits the highest predictive power when the account representative employee’s performance is also high. The findings may be utilized by Indonesian government and tax practitioners interested in to improvement the taxpayer compliance.